ELECTRONIC AGRICULTURAL MAPS FORMATION ON THE BASIS OF GIS AND EARTH REMOTE SENSING - Nazar STUPEN; Mykhailo STUPEN; Oksana STUPEN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The article is dedicated to the introduction of mapping methodology of the use of agricultural lands based on GIS and Earth remote sensing from space. In the article, the theoretical and methodical positions and features of complex agricultural mapping are formulated, the method of geo-information mapping of agricultural land holdings and land uses with the use of data of Earth remote sensing from space is developed. It is proved that the technological scheme of creation of electronic agricultural maps represents a complete cycle of creating maps and includes the following stages: the preparatory stage, the stage of fieldwork, the stage of map creation. Particular attention is paid to the stage of map formation, in which the content and database of created maps are developed. It is established that work on map layout may be performed after the steps of forming layers, processing of map symbols libraries, development, and filling of databases, and also the formation of layers of thematic elements. The content of agricultural maps is a collection of agricultural complexes, objects associated with them for agricultural development of the territory of the agricultural business, and thematic elements, used to create a complex agricultural map. An approximate content of thematic elements of the agricultural complex map, consisting of agricultural complexes and agricultural infrastructure is defined on the basis of the development of theoretical foundations. A complete list of the semantics of layers of a complex agricultural map is presented.